The miR-30 family: Versatile players in breast cancer - Su-Jin Yang; Su-Yu Yang; Dan-Dan Wang; Xiu Chen; Hong-Yu Shen; Xiao-Hui Zhang; Shan-Liang Zhong; Jin-Hai Tang; Jian-Hua Zhao (Tumor Biology)
The microRNA family, miR-30, plays diverse roles in regulating key aspects of neoplastic transformation, metastasis, and clinical outcomes in different types of tumors. Accumulating evidence proves that miR-30 family is pivotal in the breast cancer development by controlling critical signaling pathways and relevant oncogenes. Here, we review the roles of miR-30 family members in the tumorigenesis, metastasis, and drug resistance of breast cancer, and their application to predict the prognosis of breast cancer patients. We think miR-30 family members would be promising biomarkers for breast cancer and may bring a novel insight in molecular targeted therapy of breast cancer.